Slavery and dependence in ancient Egypt: sources in translation - Rowlandson, Jane (Cambridge University Press, 2024)
"Aimed at students, instructors and general readers interested in the experiences of enslaved persons in ancient Egypt, from the Old Kingdom to the early Islamic period. Provides nearly three hundred primary sources in translation, arranged both chronologically and thematically and accompanied by contextualising introductions"-- Provided by publisher